Mineral Fertilization and Maize Cultivation as Factors Which Determine the Content of Trace Elements in Soil - Marzena S. Brodowska; Mirosław Wyszkowski; Barbara Bujanowicz-Haraś (Agronomy, 2022)
This study has been carried out in order to determine the effect of increasingly intensive fertilization with potassium, applied in combination with nitrogen, on the content of trace elements in soil after the harvest of maize (Zea mays L.). The soil content of trace elements depended on the fertilization with potassium and nitrogen. Potassium fertilization had a stronger effect on the content of trace elements in the pots fertilized with the lower nitrogen dose (130 mg N kg−1 of soil). The increasing doses of potassium led to a higher soil content of zinc (Zn), and especially of nickel (Ni). The impact of potassium fertilization on the content of the remaining trace elements in the soil was less unambiguous, and depended on the dose of potassium and nitrogen fertilization. Nitrogen fertilization resulted in a higher soil content of manganese (Mn), chromium (Cr), nickel (Ni) and cadmium (Cd), as well as a decreased soil content of lead (Pb). It needs to be underlined that changes in the soil content of Ni, Cd, and Pb, effected by nitrogen fertilization, were larger than in the cases of the other trace elements. The influence of potassium and nitrogen fertilization did not result in exceeding the current threshold amounts of trace elements set for agriculturally used soil. An increase in the contents of some trace elements in soil is beneficial from an agricultural point of view. Some of these elements are necessary for the correct growth and development of arable plants.